Two-Stage Dual-Level Dispatch Optimization Model for Multiple Virtual Power Plants with Electric Vehicles and Demand Response Based on a Stackelberg Game - Jincheng Tang; Xiaolan Li (Energies)
With the continuous increase in the number of electric vehicles (EVs) and the rapid development of demand response (DR) technology, the power grid faces unprecedented challenges. A two-stage dual-level dispatch optimization model of multiple virtual power plants based on a Stackelberg game is proposed in this paper. In the day-ahead stage, a two-layer optimization scheduling model is established, where the EV layer optimizes its actions for maximum comprehensive user satisfaction, while the VPP layer optimizes its actions for minimal operating costs and interaction power, determining the scheduling arrangements for each distributed energy resource. In the intraday stage, a Stackelberg game model is constructed with the distribution network operator (DNO) as the leader, aiming to maximize profits, and the VPP as the follower, aiming to minimize its own operational costs, with both parties engaging in a game based on electricity prices and energy consumption strategies. In the simulation case study, the effectiveness of the constructed model was verified. The results show that the model can effectively reduce user costs, thereby increasing the comprehensive satisfaction of EV users by 20.7% and reducing VPP operating costs by 13.37%.